Assessment of Salivary and Serum Proteins in Patients with Oral Tumors (Baghdad Science Journal, 2025)
The qualified subjects for this study included 33 patients with benign and malignant oral tumors aged 15-75 years and 31 matched age and gender healthy subjects used as control. Proteins measurements included total protein, albumin, globulines in sera and saliva samples, and immunoglobulins (IgG, IgM, IgA) in sera samples of control and patients. Meanwhile, polyacrylamide gel electrophoresis (PAGE) was used to differentiate between protein patterns in both serum and saliva samples among the studied groups. The gel was also stained for glycoprotein to evaluate as well the changes in glycoprotein contents. For total protein, the results revealed a signifigant increase (P?0.01) in both samples (serum and saliva) of patient group. Albumin concentration shows presence of a high significant decrease (P=0.001) in sera samples but a significant increase (P